Adrenal Leiomyoma: A case report. (August 2021) - Sharma, Sujan; Timilsina, Sujan; Joshi, Surya Prakash; Bist, Anil; Shrestha, Suraj; Tiwari, Sansar Babu
Abstract: Introduction and importance: Adrenal Leiomyomas are infrequent tumors with only a few cases reported to date. They are difficult to differentiate from malignant adrenal tumors due to non-specific findings on clinical examination and imaging studies. Case presentation: We discuss the case of a 49-year old male who had been experiencing generalized abdominal pain for 14 months and was found to have a mass on ultrasonography. Further evaluation with Contrast-enhanced Computerized Tomography (CECT) revealed an uneven soft tissue density mass in the retroperitoneal region of the left side. The histopathological examination of the excised mass was suggestive of a mesenchymal tumor, which was further confirmed as leiomyoma by immunohistochemistry. Clinical discussion: Adrenal Leiomyomas are rare smooth muscle tumors that present with heterogeneously enhancing mass on radiologic imaging. On histopathological examination, spindle cells arranged in lobules and fascicles can be appreciated. Positive staining for desmin and smooth muscle actin in immunohistochemistry confirms the diagnosis. Conclusion: Identification of the type of tumor in any adrenal mass is challenging pertaining to the non-specific findings on imaging studies. So, prompt surgical resection is the mainstay of the treatment. Highlights: Adrenal leiomyomas are rare tumors. These tumors are usually identified incidentally on USG and CT scans of the abdomen & pelvis. Histopathological and immunohistochemical studies of the resected tumor mass aid in reaching a definitive diagnosis.